Fluoride levels ol'drinking water samples in hatay province - Suat Erdoğan (Eurasian Journal of Veterinary Sciences)
Fluoride ion concentration of 88 drinking water samples which were collected from twelve different province of Hatay in summer, were measured potentiometrically by using an ion ^elective electrode. The mean fluoride ion concentration was found lo be 0.174±0.016 ppm. The lowest lluoride level was detected in Belen (0.071±0.018 ppm) and the highest was measured in Reyhanlı province (0.436+0.035 ppm). Signilicant differences were seen between the fluoride ion levels of the regions (p<0.001). The fluoride ion levels of Ihe three spring water which are consumed only summer time in Erzin province were found 1.870±0.242 ppm. Except for Erzin spring water samples, other water samples was found to contain insufficient fluoride ions according lo World Health Organisalion, It was concluded that fluoride tablets should be given to the children under the supervision of dentists in Hatay province.